FAKTOR-FAKTOR YANG MEMENGARUHI PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ofira Callista; Meinie Susanty (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to analyze the effect of audit committee, institutional ownership, company size, profitability, leverage, sales growth, and capital intensity on tax avoidance. The population in this study are manufacturing companies that are consistently listed on the Indonesia Stock Exchange (IDX) during the period 2018 to 2020. The sample in this study used purposive sampling method, there were 186 years data from 62 manufacturing companies. The data analysis techniques used in this study are descriptive statistics, quality tests, assumption tests, and hypothesis testing. The results of this study indicate that profitability affects tax avoidance, while audit committee, institutional ownership, company size, leverage, sales growth, and capital intensity have no effect on tax avoidance.